A CHALLENGING CASE OF PARATHYROID CARCINOMA WITH SEVERE HYPERCALCEMIA - Wh, Wan Mohd Hafez; Ma, Masliza Hanuni (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Parathyroid carcinoma is a rare condition and it accounts for < 1% of cases of sporadic primary hyperparathyroidism (PHPT). Parathyroid carcinoma is commonly associated with severe and refractory hypercalcemia. We described a patient with parathyroid carcinoma who presented with multiple pathological fractures. RESULTS A young female presented with closed fractures of the right proximal humerus and bilateral femoral necks after a trivial fall. Her initial serum calcium was 3.18 mmol/L, serum phosphate was 0.56 mmol/L. The diagnosis of primary hyperparathyroidism was confirmed with high serum parathyroid hormone (iPTH) level of 1187.2 pg/mL (14.9-56.9). Neck ultrasound showed a right parathyroid lobulated lesion measuring 1.6 x 2.3 x 3.3 cm. The challenge in management was the refractory severe hypercalcemia despite standard treatment of hydration, bisphosphonate and calcitonin. Her serum calcium still ranged between 3.6-4.5 mmol/L despite the above therapy. She developed ECG changes typical for hypercalcemia (short QT interval). The surgery cannot proceed due to severe hypercalcemia. Hence, the decision for hemodialysis was made. She underwent 2 sessions of hemodialysis with low calcium dialysate and proceeded with emergency right inferior parathyroidectomy and right hemithyroidectomy. Postoperatively, she was put on calcium gluconate infusion for a few days on top of oral calcium supplement and oral vitamin D, in anticipation of hungry bone syndrome. Histopathological examination confirmed a right parathyroid carcinoma with infiltration to adjacent thyroid tissue. She was discharged well with oral calcium and oral vitamin D supplement. As for her multiple pathological fractures, they were treated conservatively. CONCLUSION Hypercalcemia in parathyroid carcinoma is very challenging to manage because it tends to be severe and refractory. Hemodialysis for treatment of severe hypercalcemia was shown to be effective for reduction of hypercalcemia while the patient prepare for parathyroidectomy.